2021
DOI: 10.1007/s40519-021-01232-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between social media addiction and eating disturbances is mediated by muscle dysmorphia-related symptoms: a cross-sectional study in a sample of young adults

Abstract: Purpose Although the association between problematic use of the internet and eating disorders (EDs) in young adults has been previously established, its underlying mechanisms have not been completely clarified. It has been suggested that exposure to idealized very thin and toned body images (e.g., “thinspiration” and “fitspiration” trends) on social media might lead to increased feelings of body dissatisfaction which, in turn, can represent a trigger for EDs. We have tested this hypothesis in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Relatedly, results showed that BMI was negatively correlated with SMA-related symptoms and positively correlated with IGD-related symptoms (Table S2), supporting previous studies in which different effects on eating behavior were observed in relation to SM and OVG use: problematic videogaming has been associated with sedentarism and junk food use (Hinojo-Lucena et al, 2019;Kracht et al, 2020), while problematic SM use has been associated with increased preoccupation over physical appearance (Cataldo et al, 2021;Imperatori et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Relatedly, results showed that BMI was negatively correlated with SMA-related symptoms and positively correlated with IGD-related symptoms (Table S2), supporting previous studies in which different effects on eating behavior were observed in relation to SM and OVG use: problematic videogaming has been associated with sedentarism and junk food use (Hinojo-Lucena et al, 2019;Kracht et al, 2020), while problematic SM use has been associated with increased preoccupation over physical appearance (Cataldo et al, 2021;Imperatori et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Further, the focus of the present research was specific on SMA‐ and IGD‐related symptoms and thus the findings do not apply to different types of PUI; as already mentioned, in fact, this is relevant as PUI is a wide‐ranging construct including heterogeneous phenomena (Brand et al, 2016; Fineberg et al, 2018; Griffiths & Pontes, 2014). Relatedly, results showed that BMI was negatively correlated with SMA‐related symptoms and positively correlated with IGD‐related symptoms (Table S2), supporting previous studies in which different effects on eating behavior were observed in relation to SM and OVG use: problematic videogaming has been associated with sedentarism and junk food use (Hinojo‐Lucena et al, 2019; Kracht et al, 2020), while problematic SM use has been associated with increased preoccupation over physical appearance (Cataldo et al, 2021; Imperatori et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, it provides a global severity index (GSI) that is considered to reflect the general level of psychopathology. In accordance with both previous recommendations [44] and reports [45][46][47], the cutoff point score of 63 T (on the GSI or in two psychopathological dimensions) has been used to identify individuals with a significant level of psychopathology (i.e., BSI cutoff). In the present research, a validated Italian version of BSI has been used [48], and in the current sample, the internal consistency was adequate for the BSI total score (i.e., Cronbach's alpha = 0.97).…”
Section: Questionnairesmentioning
confidence: 99%
“…According to the data above, those who spend a lot of time on social media are more likely to participate in excessive use, which can lead to behavioral and mental health problems. In the literature, excessive use of social media has been associated with decreased sleep quality, daily cognitive failures, eating problems as a result of a preoccupation with physical appearance and muscularity, and negative emotions including depression and anxiety (Xanidis and Brignell, 2016;Nguyen et al, 2020;Vidal et al, 2020;Imperatori et al, 2021;Skogen et al, 2021). The empirical evidence also suggested clinical symptom arisen from an excessive use of social media, predominantly rely on the clinical criteria of Substance-Related Addictions and Internet Gaming Disorder in DSM-5 (American Psychiatric Association, 2013;Tutgun-Ünal and Deniz, 2015;Regina et al, 2016;Shahnawaz and Rehman, 2020).…”
Section: Introductionmentioning
confidence: 99%